Pengelolaan Kelas dalam Pembelajaran Menulis Teks Berita di SMP Negeri 10 Kota Bengkulu - Annisa Dinandya Syafira; Catur Wulandari; Padi Utomo (UNIB Press, 2026)
This research aims to determine classroom management in writing news texts using qualitative descriptive methods. In this research, there are six principles of classroom management which are aspects of observation, namely warmth and enthusiasm, challenge, variety, flexibility, emphasis on positive things and instilling self-discipline. Apart from that, there are five classroom management activities which are also aspects of observation, namely student arrangement, learning place arrangement, selection of learning media, facility arrangement and selection of forms of learning activities. The method used in this research is a qualitative descriptive method. Data collection techniques use observation techniques, video recording techniques, and interviews. The results of the research show that the ability of Indonesian language teachers at SMP Negeri 10 Bengkulu City in managing the class in learning to write news texts is quite good. Indonesian language teachers have tried to apply the principles of classroom management in learning to write news texts. However, there is still one of the six principles that has not been carried out or implemented optimally by teachers. The teacher has carried out class management activities well because the teacher has implemented the five activities in class management.